Posterior circulation stroke due to vertebral artery disease in the Chinese population. Issue 7 (August 2022) - Zhang, Changqing; Li, Zixiao; Liu, Liping; Pu, Yuehua; Zou, Xinying; Yan, Hongyi; Pan, Yuesong; Zhao, Xingquan; Wang, Yilong; Wang, Yongjun
Background and purpose: Little is known about the distribution of the arteries responsible for noncardiogenic posterior circulation stroke due to vertebral artery disease in the Chinese population. Furthermore, few studies have compared the risk factors, imaging manifestations, and outcomes across different types of vertebral artery disease. Therefore, our aim was to compare the differences in the risk factors, imaging manifestations, and outcome across various types of vertebral artery disease. Methods: We prospectively enrolled 228 patients from 22 Chinese centers with noncardiogenic posterior circulation stroke due to vertebral artery disease. Vertebral artery disease was classified by the involved segments of the responsible vertebral artery, and basilar artery (BA) involvement or not. Risk factors, clinical-radiologic patterns, and outcomes were compared across different types of vertebral artery disease. Results: The intracranial vertebral artery (ICVA) was more frequently involved than was the extracranial vertebral artery (ECVA). The ICVA/ICVA + ECVA group more often presented with hypertension and higher systolic blood pressure than did the ECVA group. Compared with the single-segment-of-vertebral-artery group (SSVA), the group with multiple-segments-of-vertebral-artery (MSVA) involvement or SSVA with BA involvement had more serious clinical-radiologic patterns and worse outcomes. Multivariable Cox regression identified MSVA/SSVA + BA involvement as an independent predictor of recurrent ischemic cerebrovascular events. Conclusions: The risk factors for ICVA/ICVA + ECVA were different from those of ECVA, and the MSVA/SSVA + BA group had more serious clinical-radiologic patterns and worse outcomes.